CARING PEOPLE WITH MENTAL DISORDERS AND THEIR FAMILY MEMBERS: DIAGNOSES AND INTERVENTIONS FROM NURSING CONSULTATION - Tatiana Brusamarello; Fernanda Carolina Capistrano; Vânia Carvalho de Oliveira; Nen Nalú Alves das Mercês; Mariluci Alves Maftum (Universidade Federal do Paraná, 2013)
This descriptive, retrospective documental study aimed to describe the diagnoses and nursing interventions developed during the nursing consultation, for people with mental illnesses and their family members, in a university extension project in 2010. A systematized script was used which indicated a higher frequency of the following diagnoses: compromised family coping, insufficient recreational activities, risk for impaired link between parents and children, impaired social interaction, impaired sleep patterns, moral suffering, impaired memory, disturbed thought processes, risky health behaviors, unbalanced nutrition, and hopelessness. The nursing interventions were developed in line with each diagnosis, aimed at health education and emotional support. It was concluded that the application of nursing diagnoses and interventions for people with mental illnesses and their family members was relevant, because these interventions allow the nurse to provide directed care, based in quality and excellence.